Modification of SCE-UA genetic algorithm for runoff-erosion modelling - Santos, Celso A. G.; Suzuki, Koichi; Watanabe, Masahiro (Journal of Nepal Geological Society, 2000)
In order to provide a robust tool to be used in runoff-erosion modelling, the present paper introduces new evolution steps in the SCE-UA genetic algorithm, which is based on the simplex theory. The new evolution steps were conceived in order to improve the efficiency of such an algorithm. Thus, they will theoretically expand the simplex in a direction of more favourable conditions, or contract it if a move is taken in a direction of less favourably conditions. Hence, these new evolution steps enable the simplex both to accelerate along a successful track of improvement and to home in on the optimum conditions. Therefore, it will usually reach the optimum region quicker than the previous version and pinpoint the optimum levels more closely. The new proposed algorithm is tested with special mathematical functions, as well as in the optimisation of the erosion parameters presented in a physically-based runoff-erosion model. On the basis of these simulation results, the mean erosion parameter values are given, which agree with previous values reported to the same area. Thus, the new algorithm can be considered as a promising tool to optimise physically-based models as well as other kinds of model.